2006
DOI: 10.1111/j.1525-1438.2006.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of high-grade endometrial stromal sarcoma arising from endometriosis in the cul-de-sac

Abstract: This report describes a rare case of high-grade endometrial stromal sarcoma (ESS) arising from pathologically confirmed endometriosis in the cul-de-sac. A 37-year-old woman presented with irregular menstruation, pelvic pain, and diarrhea. Magnetic resonance imaging and colon biopsy suggested endometriotic nodule of the cul-de-sac. The tumor size was reduced with hormonal therapy, and the residual tumor was excised, resulting in the pathologic diagnosis of endometriosis. Two years later, a soft mass reappeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Extrauterine ESS exhibits similar morphologic features to its uterine counterpart and has been frequently associated with endometriosis [1,20,26,27]. However, in the absence of endometriosis or classic morphologic features, primary extrauterine ESS can present a significant diagnostic challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrauterine ESS exhibits similar morphologic features to its uterine counterpart and has been frequently associated with endometriosis [1,20,26,27]. However, in the absence of endometriosis or classic morphologic features, primary extrauterine ESS can present a significant diagnostic challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Sporadically, ESS originates as a primary tumor of extrauterine sites including the ovaries, gastrointestinal tract, pelvic wall, omentum, and vagina [20][21][22][23][24][25][26]. Extrauterine ESS exhibits similar morphologic features to its uterine counterpart and has been frequently associated with endometriosis [1,20,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Adjuvant therapy, such as radiation and chemotherapy, has been tried but has not proven to be effective. For ESS, hormonal therapy is considered to be useful, 15 but it has been suggested that the presence of estrogen and progesterone receptors in ESS is associated with sensitivity to progestin therapy. 16 The median time between hysterectomy and relapse of ESS has been reported as 5.4 years for stage I, and 9 months for stages III-IV.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 35 papers were selected. The full paper was available for 29 articles and just the abstract in 5 additional articles that provided enough information[5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36]; 1 was excluded because the abstract did not provide sufficient information and the full paper could not be obtained [37]. All these articles had been reported in international peer-reviewed journals.…”
Section: Methodsmentioning
confidence: 99%